Single-Day Simulation-Based Training Improves Communication and Psychiatric Skills of Medical Students - Amsalem, Doron; Gothelf, Doron; Soul, Omer; Dorman, Alexandra; Ziv, Amitai; Gross, Raz (Frontiers in Psychiatry, 2020)
Background – Use of standardized (or simulated) patients (SP) is considered an effective teaching method for improving clinical and communication skills. This study assesses the effect of a single-day simulated patients (SP)-based training course on medical students’ communication and basic skills in clinical psychiatry during their psychiatry rotation in a university-affiliated tertiary medical center. Methods - Forty-two third-year medical students participated. Communication and basic skills in clinical psychiatry were evaluated by a modified Four Habits Coding Scale (4HCS) and the psychiatric interview coding scale before and after SP training. An actual patient interview by the students one week after the training was evaluated by an attending psychiatrist blinded to the student’s score during the SP-based training. Self-report questionnaires on satisfaction from the training and its impact on their self-confidence were administered at the end of training. Findings - The mean pre-training 4HCS score of 33.9 increased to 52.3 post-training (p < 0.001). The mean psychiatric interview coding scale score increased from 4.33 to 5.36 (p = 0.002). The self-report questionnaire yielded a mean score of 4.21 on a 1-5 Likert scale, implying high levels of satisfaction and self-confidence. Conclusions - A single SP-based training course of medical students sufficed to improve clinical and communication skills in psychiatric settings and enhance their subjective perception of those skills.